JOB PERFORMANCE DITINJAU DARI KONFLIK PERAN GANDA, BURNOUT DAN DUKUNGAN SOSIAL KELUARGA - Anggriana, Tyas Martika; Wardani, Silvia Yula; Margawati, Tita Maela (Jurnal Penelitian LPPM (Lembaga Penelitian dan Pengabdian kepada Masyarakat) IKIP PGRI MADIUN, 2014)
Work is one of the most important aspects in the life of an adult individual. The tendency of women to work cause problems. When at work, women are faced with the demands of work, whereas when it came home, the women will be exposed to domestic roles. Conditions of discomfort experienced by individuals in living their daily activities can lead to the emergence of stress. Stress experienced by individuals who work directly with the human face as a recipient of the service referred to as burnout. To face of stressful events, individuals need a social support. This study aims to determine the influence of work-family conflict, burnout and families support to job performance. This research was conducted in Institute of Teacher Training and Education PGRI Madiun. The study was conducted by using a quantitative approach non-experimental ex post-facto. Data collection techniques used is by using a questionnaire. The data analysis technique used is the regression analysis. The results of the analysis of research data shows that there is simultaneously a significant influence work-family conflict, burnout and families support to job performance. While partial analysis showed no significant effect on the work-family conflict job performance, significant effect of burnout on job performance and significant effect of families support to job performance.Keywords: Job Performance, Work-Family Conflict, Burnout, Family Support